Assessment of the Effect of Selenium Nanoparticles on Virulence Genes Expression csgD, adrA, and gcpA of Multi-Drug Resistant Salmonella enterica - mariam Ayad; Sawsan Al-Quhli; Mahir Jassim (مجلة جامعة الانبار للعلوم الصرفة)
This study explores the use of Selenium nanoparticles (SeNPs) to combat multi-drug resistant (MDR) Salmonella enterica serovars Typhi and Typhimurium, with a focus on their biofilm formation and antibiotic resistance patterns. The research involved isolating these Salmonella serovars from clinical samples, assessing their biofilm-forming abilities using the Microtiter plate assay, and analyzing their resistance to various antibiotics. A significant finding of this study is the high propensity of Salmonella isolates to form biofilms on plastic surfaces, raising concerns for infection control and food safety. The antibiotic susceptibility tests revealed an alarming level of multi-drug resistance, particularly in isolates from immunocompromised patients. This resistance was evident against frontline antibiotics like chloramphenicol, amoxicillin, and ceftriaxone. Notably, the study demonstrates that SeNPs, when combined with antibiotics, significantly improve their effectiveness. This enhancement is particularly evident in the reduced expression of biofilm- and virulence-related genes such as adrA, gcpA, and csgD. SeNPs could be a promising approach in treating resistant Salmonella infections, offering a potential solution to the escalating problem of antibiotic resistance.Overall, the study highlights the urgent need for alternative treatments against MDR Salmonella and suggests that SeNPs might be an effective option, warranting further research for clinical application.